Do Electoral Rules Matter for Female Representation? - Paola Profeta; Eleanor Woodhouse (Center for Economic Studies and ifo Institute (CESifo), 2018)
How do electoral rules affect the representation of women? We collect panel data on the universe of Italian politicians from all levels of government over the period 1987-2013 and obtain a complete picture of the career paths of male and female politicians across the whole arc of their careers in public office. We use our unique dataset to analyse the effects on female political representation of an Italian reform which, in 2005, changed the electoral rule for national elections from (mostly) majoritarian to proportional, but did not affect sub-national level elections. We find that proportional electoral rules favour the election of women. We propose a new channel through which this result is obtained, related to the different nature of political competition in the two electoral systems: under proportional rules, parties place women less frequently in competitive seats. This is consistent with the fact that proportional systems value gender diversity more than majoritarian ones, while majoritarian systems rely on head-to-head electoral races, which are not gender neutral. We also find that electoral rules have weaker effects on female representation in geographical areas where traditional gender roles are dominant.
Keywords: H70; 330; electoral systems; majoritarian; proportional; difference-in-differences